A highly stable and scalable photosynthetic reaction center–graphene hybrid electrode system for biomimetic solar energy transduction. Issue 13 (17th March 2017) - Zhang, Haojie; Carey, Anne-Marie; Jeon, Ki-Wan; Liu, Minghui; Murrell, Travis D.; Locsin, Joshua; Lin, Su; Yan, Hao; Woodbury, Neal; Seo, Dong-Kyun
Abstract : A highly stable and scalable photosynthetic reaction center–mercapto reduced graphene oxide system has been developed for solar energy transduction. Abstract : A photosynthetic reaction center (RC)-based electrode system is one of the most promising biomimetic approaches for solar energy transduction which is a renewable and environment-friendly source of energy. However, the instability of RCs in a non-cellular environment and the unfeasible scalability of electrode materials hamper the promising application of these systems. Herein, we report a highly stable and scalable RC-electrode system in which RCs are directly immobilized on a flexible and transparent mercapto reduced graphene oxide (mRGO) electrode. RCs immobilized on a mRGO film retain their photoactivity after twenty-week storage under darkness and even after 24 h continuous illumination at room temperature under aerobic conditions. The remarkable stability and mechanical flexibility of our system offer great potential for the development of a flexible RC-based biomimetic device for solar energy transduction.